SOYBEAN DEVELOPMENT AND PRODUCTIVITY AS A FUNCTION OF POTASSIUM FERTILIZATION AND INOCULATION WITH CONDITIONING BACTERIA - da Penha Filho, Nerton; Biotech Brasil, Green; Theo Gentil, Kevin (Journal of Interdisciplinary Debates, 2021)
Soybean (Glycine max L.) is an important crop to Brazil in function of its productive potential, applicability of their products and nutritive value. The maintenance of high productivity is associated to a balanced fertilizing which promotes a higher crop potential during the cycle. This study had as objective evaluate the effect of bacterial inoculation of gender Pseudomonas, doses of potassium, and the interaction between them about the variables of soybean production. The experiment was conducted at the Center of Agricultural Sciences and Biodiversity, in Crato – CE. The experiment was realized in a randomized blocs design, in subdivided plot 4x2, with four repetitions, totalizing 32 experimental plots. First factor were four doses of potassium (0, 25, 50 e 100% of the recommended dose) and the second referred to use of inoculate of Pseudomonas gender, PotaBarvar (WITH and WITHOUT). The data were submitted to variance analysis by Test F and the average of Pseudomonas were compared by Tukey test at 5% of probability and the factor potassium dose was submitted to regression analysis. It was used the statistical program Sisvar 5.3 to the statistical analysis. The analyzed variables were plant height, height of insertion of first pod, number of branches, number of pods, number of grains per pod mass of pods, mass of 100 grains, mass of grains and productivity. To factor fertilizing just the variable number of pods and number of grains per pod presented significative results at 1 and 5% of probability, respectively. The use of highest dose shown an improve of 127% to number of pods compared to witness (0% of fertilizing) while for the number of grains per pod the response was linear decreasing. To the factor PotaBarvar, only the variables number of pods and mass of pods presented significative results, with an increase of 51,5 and 15,5%, respectively, with use of inoculation. To the interaction between the potassium doses and the inoculation with PotaBarvar, none of the variables presented significative results. Thus, it is concluded that the potassium doses provided increase to number of pods and reduction of number of grains per pod and that use of inoculation presented productive increases to some variables, showing positive effect of PotaBarvar on crop.